KEMAMPUAN BERPIKIR KRITIS MAHASISWA DALAM MENANGGAPI BERITA POLITIK PADA MEDIA SOSIAL INSTAGRAM DALAM PERSPEKTIF PENDIDIKAN KEWARGANEGARAAN (Studi Kasus Terhadap Aktivis Mahasiswa Di Lingkungan Universitas Pendidikan Indonesia) - Asep Anggi Dikarsa, - (2021)
This study aims to determine students' critical thinking skills in responding to political news on social media Instagram. This research is motivated by the use of social media Instagram among student activists in accessing political news. This research uses a case study method. Data were collected through interviews, literature and documents. The data obtained were analyzed using data reduction techniques, data presentation, and verified by triangulation techniques. The results of this study indicate that student activists have the ability to think gradually and systematically through activities and characteristics of critical thinking as an effort to develop students' abilities in responding to political news on social media Instagram in the perspective of citizenship education. Keywords: critical thinking, political news, social media, civic education